Observations on the Mechanisms of the Thermal and Photoinduced Oxidation of D-Mannitol and Fucoidan by Transition Metal Complexes and Inorganic Radicals - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Chandia-Parra, N (2011)
Sin Editorial Disponible